Packing spheres with quasi-containment conditions - Andreas Fischer; Igor Litvinchev; Tetyana Romanova; Petro Stetsyuk; Georgiy Yaskov (Journal of Global Optimization, 2024)
A novel sphere packing problem is introduced. A maximum number of spheres of different radii should be placed such that the spheres do not overlap and their centers fulfill a quasi-containment condition. The latter allows the spheres to lie partially outside the given cuboidal container. Moreover, specified ratios between the placed spheres of different radii must be satisfied. A corresponding mixed-integer nonlinear programming model is formulated. It enables the exact solution of small instances. For larger instances, a heuristic strategy is proposed, which relies on techniques for the generation of feasible points and the decomposition of open dimension problems. Numerical results are presented to demonstrate the viability of the approach.
Keywords: 510; Packing spheres; Nonstandard packing; Quasi-containment; Ratio condition; Mixed-integer nonlinear programming; Heuristic; Open dimension problem; Decomposition technique; Nonlinear programming